The Study of the Indonesian Ulama Council's (MUI) Fatwa Number 11 of 2012 Regarding the Status of Children Born out of Adultery and Their Treatment: Correlation with the Constitutional Court Decision Number 46/PUU-VIII/2010 - Susilowati, Asih (Sinergi International Journal of Law, 2024)
The status of children born out of wedlock and the treatment towards them: a study of the fatwa from the Indonesian Ulama Council (Majelis Ulama Indonesia or MUI) Number 11 of 2012 concerning the position of children born out of wedlock and its correlation with the Constitutional Court Decision Number 46/PUU-VIII/2010, a historical-sociological analysis. In reality, pregnancies outside of marriage are still prevalent in Indonesian society. Legal provisions also address marriage issues and the status of children, as stipulated in Law Number 1 of 1974 concerning Marriage, which, in Article 1, defines marriage as a spiritual and physical bond between a man and a woman. Regarding the status of children born out of wedlock and the treatment towards them, MUI issues a fatwa that emphasizes legal protection for the child. The government is obligated to protect children born out of wedlock and prevent abandonment, especially by imposing punishment on the man responsible for the birth to fulfill the child's needs. However, this does not establish paternity for the man causing the birth. The correlation with the Constitutional Court decision and the historical-sociological analysis addresses the societal need for fair rights and protection, particularly for women and children. Despite this, these considerations were not incorporated into the revision of Law Number 16 of 2019 concerning Marriage. This raises questions about the fulfillment of philosophical and sociological considerations in the formation of the Republic of Indonesia Law Number 16 of 2019 amending Law Number 1 of 1974 concerning Marriage.